Biochar-mediated changes in the microbial communities of rhizosphere soil alter the architecture of maize roots - Yan, Han; Cong, Mengfei; Hu, Yang; Qiu, Chunchen; Yang, Zailei; Tang, Guangmu; Xu, Wanli; Zhu, Xinping; Sun, Xia; Jia, Hongtao (Frontiers in Microbiology, 2022)
Aeolian sandy soil is a key resource for supporting food production on a global scale; however, the growth of crops in aeolian sandy soil is often impaired due to its poor physical properties and lack of nutrients and organic matter. Biochar can be used to enhance the properties of aeolian sandy soil and create an environment more suitable for crop growth, but the long-term effects of biochar on aeolian sandy soil and microbial communities need to be clarified. Here, a field experiment was conducted in which biochar was applied to a maize (Zea mays L.) field in a single application at different rates: CK, 0 Mg ha-1; C1, 15.75 Mg ha-1; C2, 31.50 Mg ha-1; C3, 63.00 Mg ha-1; and C4, 126.00 Mg ha-1. After seven years of continuous maize cropping, verify the relationship between root architecture and microbial communities under biochar application using a root scanner and 16S/ITS rRNA gene sequencing. The application of biochar promoted the growth of maize. Specifically, total root length, root surface area, root volume and root biomass were 13.99-17.85%, 2.52-4.69%, 23.61%-44.41% and 50.61-77.80% higher in treatments in which biochar was applied (C2, C3 and C4 treatments) compared with the control treatment, respectively. Biochar application increased the diversity of bacterial communities, the ACE index and Chao 1 index of C1, C2, C3, and C4 treatments increased by 5.83-8.96% and 5.52-8.53%, respectively, compared with the control treatment, and significantly changed the structure of the of bacterial communities in rhizosphere soil. However, there was no significant change in the fungal community. The growth of maize roots was more influenced by rhizosphere bacteria and less by fungal community. Microbial co-occurrence network revealed strong associations among rhizosphere microorganisms. The core taxa (Module hubs taxa) of the bulk microbial co-occurrence network were closely related to the total length and total surface area of maize roots, and the core taxa (Connectors taxa) of the rhizosphere soil were closely related to total root length. Overall, our findings indicate that the application of biochar promotes the growth of maize roots in aeolian sandy soil through its effects on bacterial communities in rhizosphere soil.